1979
DOI: 10.1038/bjc.1979.8
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic effect of haematoporphyrin throughout the cell cycle of the human cell line NHIK 3025 cultivated in vitro

Abstract: Summary.-Cells from the established cell line NHIK 3025 were synchronized by repeated mitotic selections. Survival of the synchronized cells after treatment with haematoporphyrin and near-UV light was measured by testing the capacity of the cells to form macroscopic colonies.The sensitivity to photodynamic inactivation was small in early G1, late S and G2. The sensitivity increased throughout late G1 and early S to a maximum in mid S. More than a 100-fold variation is found in the survival after 20 min irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…The photodynamic effect of HP on NHIK 3025 cells is cell-cycle dependent, as previously shown (Christensen et al, 1979). The cell-cycle variation of the efficiency of photodynamic inactivation resembles that of inactivation by hyperthermia, except that in the latter case a drop in the sensitivity is found during the first hours of G1 (Kim et al, 1976;Dewey et al, 1977).…”
Section: Photosensitization Iby Haematoporphyrinsupporting
confidence: 69%
“…The photodynamic effect of HP on NHIK 3025 cells is cell-cycle dependent, as previously shown (Christensen et al, 1979). The cell-cycle variation of the efficiency of photodynamic inactivation resembles that of inactivation by hyperthermia, except that in the latter case a drop in the sensitivity is found during the first hours of G1 (Kim et al, 1976;Dewey et al, 1977).…”
Section: Photosensitization Iby Haematoporphyrinsupporting
confidence: 69%
“…Our results are, however, similar to those obtained for NHIK 3025 cells exposed to photosensitizer and light, where G 1 cells were the most resistant and cells in S and G 2 phases were most sensitive (22). Photodynamic treatment acts via the formation of reactive-oxygen species (22). It is well known that UVA irradiation generates reactive-oxygen species (27)(28)(29)(30), and it is likely that such products are responsible for the lethal effect of UVA.…”
Section: Discussionsupporting
confidence: 87%
“…Cells in the mid-G 1 phase appear to be least sensitive, and those in the mid-G 2 phase appear to be most sensitive toward the lethal effect of UVA. Cell cycle differences in survival after exposure to a number of different agents have been described in the literature (22)(23)(24)(25)(26), but as far as we know no information exists about cell cycle differences in the sensitivity of cells to UVA irradiation. Our results are, however, similar to those obtained for NHIK 3025 cells exposed to photosensitizer and light, where G 1 cells were the most resistant and cells in S and G 2 phases were most sensitive (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that for some cell lines, G1 cells are the most resistant of cells in the cell cycle to photodynamic treatment (Christensen et al, 1981). However, it should be noted that the same group proposed earlier that variations found through the cell cycle for hematoporphyrin may not be caused by differences in its cellular uptake (Christensen et al, 1979). Nevertheless Gomer and Smith (1980) reported the absence of cell cycle effects suggesting the possibility of cellline dependent differences for cell age response.…”
Section: Discussionmentioning
confidence: 97%